Supra-textuality in The Sekenesse of Wymmen in Glasgow, University Library, MS Hunter 307 (ff. 149v-165v) - Esteban-Segura, María Laura (Edition Reichenberger, 2024)
This chapter takes into consideration the witness of the gynaecological and obstetrical treatise known as The Sekenesse of Wymmen held in folios 149v-165v of Glasgow, University Library, MS Hunter 307, which is a translation into the vernacular of Gilbertus Anglicus’s work. The main objective is to analyse supra-textual devices in the witness, including layout, decoration, marginalia, punctuation and other visual language in order to delimit how the information is organised and knowledge transmitted. This can shed light on the function and usability of the manuscript and can help to place it in its material and cultural context.
Edition Reichenberger autoriza el depósito del documento mencionado en el Repositorio de la UNIVERSIDAD, Repositorio Institucional de la Universidad de Málaga (RIUMA, https: //riuma.uma.es/xmlui/), (y sólo ahí), a partir de ahora, según las condiciones mencionadas. (Correo de la autora)
Keywords: Medicina medieval; GUL MS Hunter 307; The Sekenesse of Wymmen; Middle English; Medieval medicine; Supra-textuality